POTENSI RIZOBAKTERI YANG DIISOLASI DARI RIZOSFER TANAMAN PADI SEBAGAI AGEN HAYATI UNTUK MENGHAMBAT PERTUMBUHAN JAMUR Pyricularia oryzae, PENYEBAB PENYAKIT BLAS PADA TANAMAN PADI - Valente Quintao; Dewa Ngurah Suprapta; I Gede Rai Maya Temaja; Khamdan Khalimi (Journal of Agricultural Science and Biotechnology, 2015)
Rice (Oryza sativa L.) is one of the staple foods for more than 60 percent of world population. Indonesian people generally are still depending on the availability of rice to fulfill Indonesian food demand. The average of rice productivity in Indonesia is 4.56 ton/ha which is relatively lower when compared with other rice growing countries, such as Australia 8.22 ton/ha;  Japan 5.85 ton/ha and China 6.06 ton/ha. One of the causes for the low productivity of rice in Indonesia is the occurrences of rice blast disease caused by Pyricularia oryzae.  To control this disease, the farmers are still rely on the use of synthetic fungicides however this measure can not effectively control the disease,  and potentially cause the health and environmental problems. It is necessary to find an alternative measure  that save to human health as well as friendly to the environment. This study was  done to evaluate the potential use of rhizobacteria isolated from rhizospheres of rice as antagonist against Pyricularia oryzae the  cause of rice blast disease.  The result showed that five isolates of rhizobacteria namely  Xanthomonas lumininescens isolate Ch3Da, Serratia liquefaciens isolate Gh13DaB, Enterobacter agglomerans isolate Gg14DtB, Enterobacter agglomerans isolate Ch2Da, and Enterobacter agglomerans isolate Ch4BaB significantly (P<0.05) inhibited the growth of Pyricularia oryzae on potato dextrose agar (PDA) medium with inhibitory activity varied from 39.46% to 46.66%. All of these isolates produced extra cellular substances which probably responsible for the inhibitory activity. This result suggested that five isolates of rhizobacteria tested in this study can be further developed as bio-control agent to reduce the development of rice blast disease.